Upaya Pelestarian Kawasan Bersejarah Kota Pusaka Parakan, Kabupaten Temanggung - Nofika Fitasari; Rina Kurniati (Ruang, 2018)
Heritage area of Parakan is one of ancient Mataram heritage area and it was ex capital city of Menoreh. This area has so many historical relics either buildings or art. Therefore at 2015, Parakan was confirmed as heritage city by Ministry of Public Works and Public Housing (PUPR). As a heritage city, Parakan still faced several problems. There are degradation of heritage buildings, less of local government’s attention about local art. Beside that, Temanggung still do not has any regulations about conservation activity in Parakan. This research aims to know how the way conservation effort in cultural heritages in Parakan. The method used in this paper is called AHP to determine classification weight due to value of influence each variable in this research.  Land use in Parakan is dominated by trade and service area and settlement area. Those settlement consist of Kauman and Pecinan Settlement which is early establishment of Parakan City. Research output in conservation buildings shows that  the alternative of conservation in Parakan are preservation, adaptation, restoration, reconstruction, cultural transmission, and cultural revitalization.